Third-harmonic generation at interfaces with femtosecond pulses: self-focusing contribution and nonlinear microscopy - Barbano, Émerson Cristiano (2016)
Third-harmonic generation (THG) is a fundamental nonlinear optical process that has been used in different applications such as third-order nonlinear materials characterization and nonlinear microscopy. It is widely employed since the third-order nonlinearity is the most important in isotropic materials and THG occurs in all media regardless of symmetry. In the tightly focused laser beam condition THG is observed only at the materials interfaces, where the focal symmetry is broken due to the presence of two media with different refractive index and/or third-order susceptibilities. Measuring slabs of different types of optical glasses, using femtosecond laser pulses, we could explain the asymmetric THG intensity profile observed at the interfaces. The harmonic generated at the exit interface is systematically stronger than the one generated at the entrance and this phenomenon can be understood by taking into account the presence of self-focusing effects. Basically, the self-focusing reduces the beam waist radius at the exit interface, resulting in greater laser irradiance and, consequently, higher THG. This study was then extended to the interfaces of a cuvette filled with organic solvents. Such systems present four interfaces and a mixture of nonlinear processes contributions since the cuvette walls present only electronic nonlinearity and the solvents present both electronic and orientational ones. In this way, the solvents may present an additional self-focusing contribution and, due to the noninstantaneous nature of the orientational process, the self-focusing from the solvent may be influenced by the pulse duration. In this case, the THG, which is an instantaneous electronic phenomenon, can be indirectly affected by pulse duration by means of the self-focusing effect. Usually, the slow orientational contribution is not considered for materials characterization by THG which may lead to incorrect nonlinear coefficient values, that means our study is important from the fundamental physics point of view and also for applications such as materials characterization. Based on the application of THG in nonlinear microscopy, we also present a microscopy technique which makes use of spatial frequency-modulated imaging (SPIFI) with single element detection. The microscope was developed at Colorado School of Mines (CSM) during an internship. The system uses a spatial light modulator (SLM) to provide the spatial frequency modulation and permits enhanced resolution images. THG SPIFI images are shown for the first time and we also report images obtained by other nonlinear optical process. In summary, the studies presented in this PhD work are of great importance for THG fundamental understanding, materials characterization and nonlinear optical microscopy.